The Impact of Conflict Management Styles on Organizational Performance: A Comparative Analysis - Gezim Shabani; Arbëresha Behluli; Fidan Qerimi (Emerging Science Journal, 2022)
Objectives: This study aims to identify the styles of conflict management in public and private enterprises in Kosovo, measure their impacts on organizational performance, and thus fill the gap that exists between the applied style and the one that has the most impact on performance. Methods: The study used the quantitative method to answer the research questions. The study participants included 100 public and 100 private sector managers. Findings: In the private sector, the most commonly used style is compromise, while the avoidance style is the least adopted. In the public sector, managers use the dominating style for conflict management while using the obliging style the least. According to the OLS model, the obligating style explains organizational performance in the private sector, while organizational performance is explained more by the compromising style in the public sector. Novelty/improvement: This research contributes to an in-depth understanding of the association of organizational performance with conflict management styles in the private and public sectors of Kosovo. It shows through a comparative approach that organizational performance improves drastically by selecting the appropriate style of conflict management. Doi: 10.28991/ESJ-2022-06-04-07 Full Text: PDF